Influence of components of optical momentum and spin of evanescent waves on micro- and nanoobjects (Review) - Angelsky, O. V.; Zenkova, C. Yu.; Ivanskyi, D. I. (Biophysical Bulletin, 2020)
Background: Mechanical properties of light are widely used in applied areas, such as optical trapping and manipulation, sorting, deformation of biological cells and molecules. In general, the evanescent field may exhibit three components of optical momentum and spin angular momentum (spin), which manifest themselves in the occurrence of corresponding components of optical force and torque. Such extraordinary properties of evanescent waves open up new possibilities for manipulating of micro- and nanoobjects, in comparing with classical optical tweezers and manipulators, which can be used for solving the applied problems, in particular, of biomedicine.Objectives: Aim of this work is to analyze and summarize recent studies regarding to the mechanical influence of evanescent field on micro- and nanoobjects, in particular, related to the influence of transverse components of optical momentum and spin.Materials and methods: Method of momenta allows one to distinguish in an evanescent field the action of optical forces and torques, associated with the components of optical momentum and angular momentum of different nature and action direction, depending on the polarization of the incident wave. Experimental methods of particle manipulation in the near field allow visualizing such an influence, which makes it possible for solving the applied problems.Results: Recent studies demonstrate the action on nano- and microobjects of such "extraordinary" optical momentum and spin components, as transverse spin momentum, transverse spin, transverse imaginary optical momentum component, and vertical spin. Using, in particular, the latter, to solve the applied problems of biomedicine is proposed, such as transporting of therapeutic agents to pathological areas or restoring vascular patency and tissue blood supply.Conclusions: Obtained results of theoretical and experimental investigation of the mechanical action of the optical momentum and spin components of evanescent field allow us to extend the approaches of optical manipulation of micro- and nanoobjects, with the possibility of applications, in particular, for the problems of biomedicine.